Problems and challenges in relation to the treatment of patients with multimorbidity: General practitioners' views and attitudes*. (June 2015) - Søndergaard, Elisabeth; Willadsen, Tora Grauers; Guassora, Ann Dorrit; Vestergaard, Mogens; Tomasdottir, Margret Olafia; Borgquist, Lars; Holmberg-Marttila, Doris; Olivarius, Niels de Fine; Reventlow, Susanne
Abstract Objective. To explore views and attitudes among general practitioners (GPs) and researchers in the field of general practice towards problems and challenges related to treatment of patients with multimorbidity. Setting. A workshop entitled Patients with multimorbidity in general practice held during the Nordic Congress of General Practice in Tampere, Finland, 2013. Subjects. A total of 180 GPs and researchers. Design. Data for this summary report originate from audio-recorded, transcribed verbatim plenary discussions as well as 76 short questionnaires answered by attendees during the workshop. The data were analysed using framework analysis. Results. (i) Complex care pathways and clinical guidelines developed for single diseases were identified as very challenging when handling patients with multimorbidity; (ii) insufficient cooperation between the professionals involved in the care of multimorbid patients underlined the GPs' impression of a fragmented health care system; (iii) GPs found it challenging to establish a good dialogue and prioritize problems with patients within the timeframe of a normal consultation; (iv) the future role of the GP was discussed in relation to diminishing health inequality, and current payment systems were criticized for not matching the treatment patterns of patients with multimorbidity. Conclusion. The participants supported the development of a future research strategy to improve the treatment of patients with multimorbidity. Four main areas were identified, which need to be investigated further to improve care for this steadily growing patient group.